Pengaruh Lama Perendaman Daging Kambing Kombinasi Larutan Belimbing Wuluh (Averrhoa bilimbi L) dan Daun Pepaya (Carica papaya L) terhadap KualitasFisik dan Organoleptik - Rahayu, Tri Puji; S, Sapbtia; Nugraheni, Martha Arum (Unpad Press, 2023)
Goat meat has a hard texture and strong aroma so that the level of public liking is low. Wuluh starfruit and papaya leaves have active substances that can maintain the physical and organoleptic qualities of goat meat. This experiment was designed to determine the effect of soaking time on the combination of wuluh starfruit and papaya leaves on the physical and organoleptic qualities of goat meat. The study was a Completely Randomized Design (CRD), with 4 treatments (a combination of 40% concentration of wuluh starfruit and papaya leaves solutions with immersion times of 0, 20, 40 and 60 minutes). Each treatment was repeated 5 times. The variables observed included physical quality and organoleptic tests. Data analyzed using the Normality test, normally data using analysis of variance (ANOVA) at a real level 5% and significant differences between treatments were analyzed using Duncan's test. Abnormal data will be analyzed with the Kruskal Walis test. The results showed that soaking time had a significant effect on pH, water holding capacity, cooking loss, color, texture and taste but had no effect on the flavor of goat meat. Soaking time of 60 minutes is effective in lowering the pH value by 39.6%, increasing the water holding capacity by 25%, reducing cooking losses by 29.5%, making the texture of the meat tender and no change in flavor from meat. Soaking for 20 minutes produces a red color and a non sour and non bitter taste